IMPROVING ABILITY IN WRITING PROCEDURE TEXT THROUGH PICTURES AT THE TENTH YEAR SRUDENTS OF SMAN 3 POLEWALI MANDAR - Muthmainnah Muthmainnah (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2015)
The objective of this research is to find out whether or not the using of pictures improve student’s ability in writing procedure text at the tenth year students of SMAN 3 Polewali .To obtained the data the writer used pre experimental method with a pre-test and post-test. It is used to show whether pictures improve students ability in writing procedure text or not. The population of this research was the tenth class students of SMA Negeri 3 Polewali in academic year 2014/2015 which consist of four classes (A,B,C,D) and 150 students. This research employs cluster sampling technique because the number of the population was relatively large. The writer chooses 40 students from class B. Based on data anlysis from students writing procedure text by using picture, the data shows that the highest student’s score obtained from the pre-test is 70, classified as good score and the lowest score is 34, classified as very bad score writing skill without using picture of the tenth year students of SMAN 3 Polewali falls into the fair category mean score is 63.15. It means that the using of pictures improve the students’ ability in writing procedure text at the tenth year students of SMAN 3 Polewali because the means score of the post-test 75.22 is higher than the mean score of the pre-test . So, the hypotesis the using of pictures improve the ability in writing procedure text of the tenth year students of SMAN 3 Polewali was accepted.